Immunohistochemistry for detection of infectious agents through antibody-antigen biomarker interaction in formalin-fixed paraffin-embedded tissues - Fitzwater, Shawna E. (Kansas State University, 2021)
Immunohistochemical detection of antigen distribution within infected formalin-fixed paraffin-embedded (FFPE) tissues is an extremely specific and complex procedure that is still relatively new in diagnostic pathology. New and improved techniques that aid to improve the sensitivity and specificity of an immunohistochemical (IHC) test are required for a more accurate etiologic diagnosis. The objective of this research study was to evaluate IHC protocol development techniques and procedures on FFPE biological tissues to improve biomolecular antibody-antigen detection using chromogenic enzymes. This study provides evidence suggesting that multiple factors play a significant role on the outcome of an accurate IHC test; pH and purified antibody concentration being among the most prominent. In addition, diminishing testing development associated costs, while reducing diagnostic turn-around time is attainable through a standardized approach to the protocol development process, resulting in efficient and accurate IHC detection of infectious agents in tissue sections.
Keywords: Immunohistochemistry; Infectious agent